PENERAPAN MODEL PICTURE AND PICTURE UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI DI SEKOLAH DASAR - Amelia, Rizky; Halidjah, Siti; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to determine the improvement of writing description skills on learning Indonesian language Â through the application of picture and picture model of fourth grade students of Elementary School Negeri 9 Pontianak Utara. The research method used is descriptive method. The subject of the study were 37 students. This study was conducted 3 cycles, the results showed that the ability of teachers to design learning from cycle I obtained the average of 3,4 cycle II obtained an average value 3,69 and cycle III obtained an average value of 3.85, while the ability of teachers to implement learning from the results of cycle I obtained an average value of 3,21, cycle II obtained an average value of 3.52 and cycle III obtained an average value of 3.72. The result of writing writing essay description of students in cycle I, with score average 62,01. In cycle II, the average was 74.47 and the average cycle III of 78,83. Thus, the picture and picture model can improve the student writing description skill.Â Keywords: picture and picture model, writing skill descriptionÂ